Associations of IL13 gene polymorphisms and immune factors with Schistosoma haematobium infection in schoolchildren in four schistosomiasis-endemic communities in Ghana. - Margaret Sarpong-Baidoo; Michael F Ofori; Elias Kwesi Asuming-Brempong; Eric Kyei-Baafour; Bright K Idun; Isaac Owusu-Frimpong; Nana A Amonoo; Queenstar D Quarshie; Edward J Tettevi; Mike Y Osei-Atweneboana (Public Library of Science (PLoS), 2021)
Background Schistosomiasis remains a major public health issue with over 90% of the prevalence rates recorded in Sub-Saharan Africa. In this study, the relationships between different interleukin gene polymorphisms (IL-13-591A/G, IL-13-1055C/T, IL-13-1258A/G) and Schistosoma haematobium infection levels were evaluated; as well as the host plasma antibodies and cytokine profiles associated with schistosomiasis infection. Methodology A total of 469 school children aged 6 to 19 years from four schistosomiasis-endemic communities in Ghana were involved. Single urine and stool samples were obtained from each pupil, processed via sedimentation and Kato-Katz, and examined via microscopy for Schistosoma and soil-transmitted helminth (STH) eggs. Next, venous blood samples were drawn from 350 healthy pupils, and used to measure antibody and plasma cytokine levels by ELISA. Single nucleotide polymorphisms in the IL-13 gene were genotyped on 71 selected blood samples using the Mass Array technique. Principal findings and conclusion The overall prevalence of urinary schistosomiasis was 21.11%. Community-level prevalences were 17.12%, 32.11%, 20.80%, and 15.32% for Asempaneye, Barikumah, Eyan Akotoguah, and Apewosika respectively. Generally, higher S. haematobium infection prevalence and intensity were recorded for participants with genotypes bearing the IL13-1055C allele, the IL13-591A, and the IL13-1258A alleles. Also, higher S. haematobium infection prevalence was observed among participants in the 12-14-year age group with the IL13-1055C, IL13-591A, and IL13-1258A alleles. Interestingly, higher STH prevalence was also observed among participants with the IL13-1055C, IL13-591A, and IL13-1258A alleles. Furthermore, the age-associated trends of measured antibodies and cytokines of S. haematobium-infected school-children depicted a more pro-inflammatory immune profile for pupils aged up to 1l years, and an increasingly anti-inflammatory profile for pupils aged 12 years and above. This work provides insight into the influence of IL-13 gene polymorphisms on S. haematobium, and STH infections, in school-aged children (SAC).